2016
DOI: 10.1097/ccm.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

The Postcardiac Arrest Consult Team: Impact on Hospital Care Processes for Out-of-Hospital Cardiac Arrest Patients*

Abstract: Implementation of a Post-Arrest Consult Team reduced premature withdrawal of life-sustaining therapy but did not improve rates of successful targeted temperature management, coronary angiography, formal electrophysiology assessments, or functional survival for comatose patients after out-of-hospital cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A total of 21 observational studies 183,184,[188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] and 1 pilot randomized trial 207 were included in the SR. 10 Of these, 17 observational studies were ultimately included in meta-analysis. 183,184,[188][189][190][191][192][193][194][199][200][201][202][203][204][205][206] All studies were in OHCA cohorts; 1 study 195 also included patients with IHCA, but outcomes were not reported separately.…”
Section: [H3]consensus On Sciencementioning
confidence: 99%
“…A total of 21 observational studies 183,184,[188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] and 1 pilot randomized trial 207 were included in the SR. 10 Of these, 17 observational studies were ultimately included in meta-analysis. 183,184,[188][189][190][191][192][193][194][199][200][201][202][203][204][205][206] All studies were in OHCA cohorts; 1 study 195 also included patients with IHCA, but outcomes were not reported separately.…”
Section: [H3]consensus On Sciencementioning
confidence: 99%
“…110 Some initiatives at the federal level grant immunity from civil liability not only to lay rescuers but also to AED device owners under certain circumstances. 111…”
Section: Innovative Approaches To Public-access Defibrillationmentioning
confidence: 99%
“…110 Some initiatives at the federal level grant immunity from civil liability not only to lay rescuers but also to AED device owners under certain circumstances. 111 The Chase McEachern Act in Ontario, Canada, protects from civil liability the defibrillator user, the owner of the equipment, and the premises on which it is located, as well as health care professionals outside a health care facility. 112 Other countries such as South Korea, Taiwan, and Japan also have Good Samaritan laws that protect bystander rescuers from civil liability when performing CPR or using an AED.…”
Section: Addressing Perceived and Real Legal Barriersmentioning
confidence: 99%
“…A total of 21 observational studies 183,184,[188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] and 1 pilot randomized trial 207 were included in the SR. 10 Of these, 17 observational studies were ultimately included in meta-analysis. 183,184,[188][189][190][191][192][193][194][199][200][201][202][203][204][205][206] All studies were in OHCA cohorts; 1 study 195 also included patients with IHCA, but outcomes were not reported separately.…”
Section: [H3]consensus On Sciencementioning
confidence: 99%